2020
DOI: 10.1007/s10072-020-04376-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor mutations and clinical sensitivity to glucocorticoid in Chinese multiple sclerosis patients

Abstract: Background Glucocorticoid (GC) is the first-line therapy in acute attacks of multiple sclerosis (MS), but its efficacy is individually variable and may be associated with glucocorticoid receptor (GR) gene. Objective To establish the association between GR gene sequence and clinical GC sensitivity in Chinese MS patients. And to investigate the expression differences of serum GRα and FK506 binding protein 5 (FKBP5) in GC responders and non-responders. Materials and methods Coding exons 2-9 of the GR gene from 97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…FKBP5 protein, a newly identified protein with an abnormal expression in MS progression, has been reported to accumulate in human MS (26,27), but it is not clear what the physiological role and mechanism of FKBP5 are in CPZ pathogenesis. In this study, we found that FKBP5 is crucial for the progression of myelin loss and regeneration by activating the PINK1-Parkin mitophagy pathway, in which the important regulator, PPAR-γ, is critically regulated by FKBP5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FKBP5 protein, a newly identified protein with an abnormal expression in MS progression, has been reported to accumulate in human MS (26,27), but it is not clear what the physiological role and mechanism of FKBP5 are in CPZ pathogenesis. In this study, we found that FKBP5 is crucial for the progression of myelin loss and regeneration by activating the PINK1-Parkin mitophagy pathway, in which the important regulator, PPAR-γ, is critically regulated by FKBP5.…”
Section: Discussionmentioning
confidence: 99%
“…Mitophagy is one of the molecular mechanisms that have been linked to MS. Recent studies have found that the FKBP5 levels in the cerebrospinal fluid and peripheral blood of MS patients were significantly upregulated, suggesting that FKBP5 plays an important role (26,27). However, few studies have focused on mitophagy regulation by FKBP5 in demyelinating diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The second-line therapy is plasma exchange. 272 A study explored the factors associated with the efficacy of glucocorticoid in Chinese patients with MS. 273 The results showed that patients who were sensitive to glucocorticoid had higher expression of glucocorticoid receptor (GR)-α and lower expression of FK506 binding protein 5 (FKBP5), which might provide a novel therapeutic strategy for glucocorticoid-resistant patients with MS in the acute stage.…”
Section: Treatmentsmentioning
confidence: 99%